Effect of cold compaction pressure and sintering temperature on the densification and microstructure of 316L stainless steel powder - Ayman Mahmoud Fahim; Tamás Mikó; Mohamed Zaky Ahmed; Zoltán Gácsi (Results in Engineering, 2025)
Austenitic stainless steel 316 L is widely used for several structural, industrial, and biomedical applications due to its outstanding corrosion resistance, good strength, ductility, and biocompatibility compared to counterparts. This study investigates the effect of different cold compaction pressures and sintering temperatures on densification and microstructure evolution of consolidated 316 L powder. Compaction pressures ranging from 600 to 1600 MPa were applied to obtain cold compacts of 8 mm diameter and approximately 10 mm height. Sintering at temperatures of 1150–1300 °C for 60 min was applied. After cold compaction and sintering, the produced samples were characterized in terms of densification, hardness, and microstructure evolution. Densification was examined through Archimedes density measurement. Microstructure was examined using scanning electron microscopy. Additionally, electron backscatter diffraction (EBSD) was used to investigate grain structure and texture. For samples compacted at 1200 MPa, grain size increased from 17.1 µm at 1150 °C to 60.7 µm at 1300 °C, while twin boundary fraction decreased from 44.22 % to 5.36 %. Maximum hardness of 160 HV along with compressive yield strength of 299 MPa were recorded at 1150 °C and 1600 MPa compaction pressure, while maximum density of 97.0 % was achieved at 1300 °C at the same pressure. Results indicate that 1150 °C and 1600 MPa presents the most promising balance between densification and mechanical properties. The direct correlation between relative density and mechanical properties confirms that densification plays a dominant role in strengthening at lower sintering temperatures, whereas at higher temperatures, microstructural factors such as grain growth and reduced twinning limit further improvements.